Radio Frequency Ablation of right sided accessory pathway - 8 years experience at SGNHC - Raut, R; KC, MB; Rajbhandari, S; Dhungana, M; Shah, R; Shah, KB (Nepalese Heart Journal, 2013)
Background Radiofrequency ablation has been established as the curative treatment for most of supraventricular tachycardia since 1987. In SGNHC, ablation has been done routinely since 2003. In our experience, right sided accessory pathway (AP) has been technically difficult and challenging with low success rate as mentioned in literature outside. So, the objective of this article was to analyze the demographic characteristics, success and recurrence rate and complication of right sided AP ablation in our centre. Methods and Materials From 13th Oct 2003 to 9th Sept. 2011, altogether 768 patients who underwent ablation were analyzed. Result Among 768 patients, 416(54.2%) were accessory pathways out of which 72(17.3%) were right sided AP. Majority of right sided accessory pathway were manifest (WPW) comprising 77.1%, significantly higher compare to left sided pathway where manifest AP was only 44.1 % (p< 0.001). Among all attempted ablation of right sided AP, 11 ablations failed so that the success rate was 84.7% lower than that of left sided pathway where success rate was 98.4% (p<0.001). Among 61 successful ablations, 2 relapsed during follow up period, recurrence rate being 3.3%. Although there were few complications in the ablation of other tachyarrhythmia, there was no complication noted during the ablation of 72 right sided AP. Conclusion Right sided pathway are mostly manifest. The success rate of right sided pathway is lower in comparison to left sided pathway. Our success rate is comparable to the result in the literature which indicates that ablation of right sided accessory pathway in our centre is reasonably good. DOI: http://dx.doi.org/10.3126/njh.v8i1.8332 Nepalese Heart Journal Vol.8(1) 2011 pp.19-22